Salvage pathway of vitamin B12 absorption in chickens with mutant tumor virus a receptor - Yun Ji Shin; Jin-Kyoo Kim; Seung Je Woo; Byung Chul Park; Jae Yong Han (Poultry Science)
The tumor virus A receptor (TVA), a member of the low-density lipoprotein receptor (LDLR) family, serves as an entry receptor for Avian Leukosis Virus (ALV) subgroups A and K, as well as a receptor for vitamin B12 bound to transcobalamin. Naturally occurring genetic variants in the TVA gene determine susceptibility or resistance to ALV-A and -K, but the effects of these mutated TVA on vitamin B12 uptake have not been investigated systemically. We found four TVA variants comprising the wild type (TVAWT), a single nucleotide polymorphism variant (TVASNP), and two partial deletions in the splicing branch point region (TVAR). This study investigates the relationship between the various genotypes of TVA alleles and uptake of vitamin B12 in chickens. A protein interaction model suggested that mutant TVAs (i.e., TVASNP, TVAR) may have reduced ability to take up vitamin B12 due to a disrupted LDL-A domain, a pivotal region involved in vitamin B12 uptake; however, we found no significant difference in absorption of vitamin B12 in TVAWT and TVASNP chickens, or levels of its metabolite in serum. Notably, TVAR chickens had significantly higher levels of vitamin B12 than TVAWT chickens, a finding contrary to the predicted lower uptake. Expression of vitamin B12 carrier related genes (i.e., AMN, GIF, and TCN2) in chickens showed a stepwise increase: TVAWT > TVASNP > TVAR. These results suggest a mechanism by which mutant TVA chickens with a disrupted TVA protein acquire natural resistance to ALV-A -K, with no impairment of vitamin B12 metabolism.